Japan's emerging youth policy : getting young adults back to work - Toivonen, Tuukka H. I. (Tuukka Hannu Ilmari), 1979- (New York : Routledge, 2013)
"From the 1960s onwards, Japan's rapid economic growth coincided with remarkably low youth unemployment. However, since the 1990s the ease with which young people have historically moved from education to employment has ended, and unemployment is now a real and growing problem in contemporary Japan. This book examines how the state, experts, the media as well as youth workers, have responded to the troubling rise of youth joblessness in 21st century Japan. The answer that emerges from this analysis is as complex as it is fascinating, but comprises two essential elements. First, instead of institutional 'carrots and sticks' as seen in Europe, actors belonging to mainstream Japan have deployed controversial labels such as NEET ('Not in Education, Employment or Training') to steer inactive youth into low-wage jobs. However, a second approach has been crafted by entrepreneurial youth support leaders that builds on what the author refers to as 'communities of recognition'. As demonstrated at real sites of youth support, one such methodology consists of 'exploring the user' (i.e. the support-receiver) whereby complex disadvantages, family relationships and local employment contexts are skilfully negotiated. It is this second dimension in Japan's response to youth exclusion that suggests sustainable solutions to the employment dilemmas that virtually all post-industrial nations currently face but which none have yet seriously addressed. Based on extensive fieldwork draws on both sociological and policy science approaches, this book will be welcomed by students scholars and practitioners of Japanese, East Asian and comparative social policy, welfare, culture and society"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Youth -- Employment -- Government policy -- Japan; Youth -- Employment -- Japan; Unemployment -- Japan; Youth -- Japan -- Social conditions; Electronic books